Your health service in danger (1945)
1945 1945 1940s 5 pages The Voluntary Hospitals Case More subtle and even more dangerous is the attack by the British Hospitals Association, which is prepared to accept the need for a new service so long as the voluntary hospitals get public money without public control. They have suggested a form of administration which would give them almost complete control over the local authority hospitals. This is supported by many specialists, who obtain a large proportion of their income through their connection with the voluntary hospitals. The White Paper proposals were extremely generous to the voluntary hospitals and were designed to preserve the identity of those that can still attract enough in voluntary gifts to justify the name and which could provide a service up to national standard. The number likely to be able to do so is small, since only 50 out of 700 have 200 beds or more; and if standards of hospital care and equipment are on a sufficiently high level (that of our best teaching or municipal hospital of 600-1,000 beds), much public money will have to be spent in bringing up-to-date the "cottage" type of hospital. A National Health Service A health service should be able to take care of every citizen throughout life and at every stage of life, but the White Paper did not propose a complete unification and this lack of unification would prevent some of the best developments visualised in the programmes of the Labour Party and the S.M.A., but even the minor degree of unification suggested, the setting up of Joint Authorities for hospital, specialist and planning purposes has been seen by some of the smaller local authorities as a threat to them and strong pressure has been brought to bear on the Government to modify the scheme so as to leave some of the services, e.g., existing clinics and even the hospitals, in the hands of those local authorities who at present control them. If the Government gives way to all these forces the people, and especially the wives, mothers and children of the insured workers, are going to be forgotten completely and will be no better off than to-day. Faced with demands to weaken the White Paper, there is only one attitude possible for the workers — they must demand that it is strengthened and brought into line with the needs of the sick and injured, whatever their social class. Those needs are for a single national health service, complete from general practitioner to the fullest hospital care with every type of specialist, with Health Centres in every district and with all health workers employed by the one public authority and working as a team to give the best service to all. LET YOUR VOICE BE HEARD WRITE TO YOUR M.P. WITHOUT DELAY Pass on this Leaflet Rouse Public Opinion by Meetings (Apply S.M.A. for Speakers) Issued by the SOCIALIST MEDICAL ASSOCIATION 59 New Oxford Street, London, W.C.1 Speedee Press Services Ltd. (T.U. all depts.). 27A, Pembridge Villas, W.11. Extra copies, post free, 2/6 per 100, £1 per 1,000 292/847/3/131